Фондовий та криптовалютний ринки: ключові домінанти розвитку в Україні - Застьола, Євген Олексійович; Савченко, Роман Олегович; Бріль, М. С. (Видавничий дім "Гельветика", 2025)
У статті проведено дослідження фондового та криптовалютного ринків України з метою виявлення основних тенденцій та особливостей їхнього функціонування. Доведено, що фондовий та криптовалютний ринки є елементами фінансового сектора економіки, розвиток якого впливає на ефективність національної фінансово-господарської системи. Встановлено, що на сучасному етапі доцільно приділяти підвищену увагу виявленню домінантів розвитку фондового та криптовалютного ринків, які можуть стати основою покращення макро-економічної стабільності. Проаналізовано динаміку основних показників, що характеризують обсяг випуску емісійних цінних паперів, а також, обсяг діяльності організаторів торгівлі цінними паперами в Україні. Досліджено зміну місця України в Глобальному індексі впровадження криптовалюти у 2020-2024 роках. Виявлено основні закономірності змін показників розвитку фондового та криптовалютного ринку, дана їхня порівняльна характеристика та окреслено ключові домінанти їхнього розвитку в сучасних умовах.

The article studies the stock and cryptocurrency markets of Ukraine in order to identify the main trends and features of their functioning. It was established that in the process of continuous development of the national economy, transformation affcts all spheres of the economy, both the real and the fiancial sector of the country. It was proven that the stock and cryptocurrency markets are elements of the fiancial sector of the economy, the development of which affcts the effiency of the national fiancial and economic system. It was established that at the present stage it is advisable to pay increased attention to identifying the dominants of the development of the stock and cryptocurrency markets, which can become the basis for improving macroeconomic stability. The purpose of the study was to analyze the main trends in the development of the stock and cryptocurrency markets of Ukraine and identify the dominants of their further development. During the study, methods of dynamic analysis were used to identify trends in the development of the stock and cryptocurrency markets, comparative analysis – to compare them by key parameters, logical generalization – to identify the dominants of the development of these types of markets in modern conditions. The dynamics of the main indicators characterizing the volume of issuance of securities, as well as the volume of activities of securities trading organizers in Ukraine, were analyzed. The change in Ukraine’s place in the Global Cryptocurrency Implementation Index in 2020-2024 was studied. The impact of certain factors on the functioning of the stock and cryptocurrency markets, in particular those related to martial law in Ukraine, was determined. The main patterns of changes in the development indicators of the stock and cryptocurrency markets were identifid, their comparative characteristics were given, and the key dominants of their development in modern conditions were outlined. It was established that the parallel synchronized development of the stock market and the cryptocurrency market will allow the population and the business sector to diversify their investment portfolio and ensure their safe placement.
Stock and cryptocurrency markets: key dominants of development in Ukraine
Keywords: фінансовий сектор; фондовий ринок; криптовалютний ринок; цінні папери; криптовалюта; домінанти розвитку; fiancial sector; stock market; cryptocurrency market; securities; cryptocurrency; development dominants